2023
DOI: 10.1002/ajim.23466
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of workplace risk for Covid‐19 in Canadian healthcare workers and its relation to vaccination: A nested case‐referent study

Abstract: Background During the early months of the Covid‐19 pandemic, studies demonstrated that healthcare workers (HCWs) were at increased risk of infection. Few modifiable risks were identified. It is largely unknown how these evolved over time. Methods A prospective case‐referent study was established and nested within a cohort study of Canadian HCWs. Cases of Covid‐19, confirmed by polymerase chain reaction, were matched with up to four referents on job, province, gender, and date of first vaccination. Cases and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
(54 reference statements)
4
13
0
Order By: Relevance
“…An excess risk in HCW relative to the community during the Omicron wave has been reported from Hong Kong, comparing infection rates in staff from a single hospital to that in the general population [16], but not more widely. Our earlier work has shown that while risk of work-related Covid-19 decreased after vaccination it did not disappear completely [6] and it seems feasible that, with a surge in infection in the population, HCWs were again at greater risk, as suggested here. The increase in risk of a diagnosis of a stress/adjustment reaction or a depressive condition from the start of the pandemic to the fourth wave (to late fall 2021) is unlikely to be due to chance.…”
Section: Discussionsupporting
confidence: 58%
“…An excess risk in HCW relative to the community during the Omicron wave has been reported from Hong Kong, comparing infection rates in staff from a single hospital to that in the general population [16], but not more widely. Our earlier work has shown that while risk of work-related Covid-19 decreased after vaccination it did not disappear completely [6] and it seems feasible that, with a surge in infection in the population, HCWs were again at greater risk, as suggested here. The increase in risk of a diagnosis of a stress/adjustment reaction or a depressive condition from the start of the pandemic to the fourth wave (to late fall 2021) is unlikely to be due to chance.…”
Section: Discussionsupporting
confidence: 58%
“…Participants were recruited early in the pandemic and completed the following four online questionnaires: phase 1 in spring/summer of 2020, phase 2 in fall of 2020, phase 3 in spring of 2021, and phase 4 in spring of 2022. Information on positive tests for COVID-19 was collected in the questionnaire completed at each phase and, for a nested case-referent study, 15 by self-reports between questionnaires. From December 2020, when vaccination against COVID-19 became available to Canadian healthcare workers, information on dates and type of vaccine was collected alongside data on infection.…”
Section: Methodsmentioning
confidence: 99%
“…Both cases and referents were asked, in the days immediately following case infection, to complete a detailed exposure questionnaire about experiences and exposures in the days leading up to the case's positive test. More details are given in Cherry et al [3].…”
Section: Nested Case-referent Studymentioning
confidence: 99%
“…Of 542 cases eligible for the case-referent study,534 (99%) completed the case-referent questionnaire. Among 1815 selected referents 1697 (93.5%) completed [3].…”
Section: Participation In the Case-referent Studymentioning
confidence: 99%
See 1 more Smart Citation